Formula and preparation process of antistatic PC plastic particles

By mixing polycarbonate, PMMA and PETG and introducing electrostatic dissipative agents and flame retardants, antistatic PC plastic particles are prepared, which solves the problems of stress cracking of polycarbonate in polar solvents and reducing mechanical properties of flame retardants. The effect of improving corrosion resistance, solubility resistance and antistatic properties is achieved.

CN119242016AInactive Publication Date: 2025-01-03ZHEJIANG HENGMEI NEW MATERIALS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411775941.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-05
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polycarbonate plastics are prone to stress cracking and swelling in polar solvents, and the addition of flame retardant reduces its mechanical properties, resulting in static accumulation and damage to electronic devices.

Method used

Mix polycarbonate, PMMA and PETG, and introduce electrostatic dissipative agents such as conductive carbon black, activated carbon fiber and carbon nanotubes, combined with an appropriate amount of flame retardant and toughener, and mix by drying, heating, heating, and plasticizing. and extrusion granulation process to prepare antistatic PC plastic particles.

Benefits of technology

It improves the corrosion resistance, solubility and toughness of plastic particles, prevents the flame retardant from reducing tensile strength and bending strength, enhances the antistatic properties, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119242016A_ABST
    Figure CN119242016A_ABST
Patent Text Reader

Abstract

The invention discloses a formula and a preparation process of antistatic PC plastic particles, and relates to the technical field of functional plastics, the formula of the antistatic PC plastic particles comprises the following components by weight: 40-70 parts of polycarbonate, 15-40 parts of PMMA, 15-40 parts of PETG, 1-10 parts of a static dissipative agent, 0.1-0.6 part of an antioxidant, 0.2-1 part of a lubricant, 6-15 parts of a flame retardant, 2-5 parts of a flexibilizer, and 2-10 parts of a compatilizer. The static dissipative agent can adsorb flame retardant molecules, the collision between the flame retardant and other high-molecular organic matters in the formula is reduced, the flame retardant molecules are prevented from reducing the tensile strength and bending strength of the PC plastic particles, the corrosion resistance to acid, alkali, salt and other chemical substances is enhanced by adding PMMA, and the PETG plastic particles have better fluidity in the processing process, so that the flame-retardant PC plastic particles have better mechanical properties. By mixing PC, PMMA and PETG, advantage complementation among the materials is realized, the static dissipative agent is introduced, and the anti-static PC composite material with corrosion resistance, solubility resistance and strong toughness is prepared through the preparation process.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of functional plastics, and in particular to a formula and a preparation process of antistatic PC plastic particles. Background Art

[0002] Plastic particles are the common name for plastic particles. They are the raw materials for storage, transportation and processing of plastics in the form of semi-finished products. Plastic particles are often placed in an injection molding machine, heated and melted, and the molten plastic is added to the mold and cooled to form. The molded plastic model has the same properties as the plastic particles. Therefore, plastic particles with different functional properties are continuously researched and developed, playing an important role in various fields.

[0003] Polycarbonate (PC) is a thermoplastic engineering plastic with excellent comprehensive performance. It has the characteristics of high temperature resistance, flame retardancy, good electrical insulation, dimensional stability, non-toxicity, tastelessness, and easy coloring. It can be directly applied to most electrical accessories and is one of the most widely used insulating materials in electronic and electrical products. However, PC has high melt viscosity, poor fluidity, sensitivity to notches, easy stress cracking, and poor resistance to organic chemicals. At the same time, polycarbonate has high light transmittance, with a transmittance of more than 87% and up to 90%. This makes it widely used in the field of transparent materials, but long-term exposure to ultraviolet light will cause yellowing, degradation, and brittleness due to light oxidation reactions. Therefore, when used outdoors, light stabilizers, heat stabilizers, etc. need to be added to improve its performance. Using PC with high transparency as the raw material for the outer shell of electrical products allows the working conditions of electrical products to be seen.

[0004] PMMA, whose Chinese name is polymethyl methacrylate, is a kind of organic glass with high transparency and looks like glass. It is an amorphous transparent plastic with high transparency, easy processing, and resistance to a variety of chemicals, such as acid, alkali, salt, etc. However, PMMA itself has poor impact resistance and low surface hardness, which limits its application to a certain extent. However, the solubility of PMMA and PC is relatively close, and the two have good compatibility. After blending, their respective advantages can complement each other; however, PMMA and PC have poor solubility in polar solutions, and are prone to stress cracking and swelling in polar solvents; 1,4-cyclohexane dimethanol terephthalate (PETG) is a transparent, non-crystalline copolyester. G has the advantages of excellent solvent resistance, low molding temperature, easy molding processing, strong coloring power, good hygiene, etc., and belongs to a new generation of environmentally friendly plastics. The combination of PC, PMMA and PETG enhances the corrosion resistance of PC materials on the one hand, and improves the processing fluidity and solvent resistance of PC materials on the other hand, realizing the complementary advantages between materials and meeting the wider industrial needs of products.

[0005] Studies have found that the addition of many flame retardants will significantly reduce the mechanical properties of PC materials, such as tensile strength and flexural strength. This is mainly because flame retardants change the chemical molecules of plastics. Static electricity has potential damage risks to many electronic devices and precision instruments, such as causing circuit damage or data loss. Some conductive agents such as carbon black can prevent this from happening. Carbon black has similar properties to activated carbon and may adsorb flame retardant molecules, thereby preventing flame retardants from changing the chemical molecules of plastics. Summary of the invention

[0006] The present invention is made in view of the above problems, and its purpose is to provide a formula and preparation process of antistatic PC plastic particles. By mixing PC, PMMA and PETG, the complementary advantages among the materials are achieved. On this basis, an electrostatic dissipator is introduced, and the charge generated by the material during friction can be transmitted in time, so that there is no charge accumulation to generate static electricity. The effects of different flame retardants and toughening agents on the effect of the electrostatic dissipator are compared, and an antistatic PC composite material with corrosion resistance, solubility resistance and strong toughness is produced.

[0007] The technical solution adopted by the present invention is as follows: In a first aspect, the present invention provides a formula of antistatic PC plastic particles, wherein the raw materials include the following components by weight: 40-70 parts of polycarbonate, 15-40 parts of PMMA, 15-40 parts of PETG, 1-10 parts of static dissipative agent, 0.1-0.6 parts of antioxidant, 0.2-1 parts of lubricant, 6-15 parts of flame retardant, 2-5 parts of toughening agent, and 2-10 parts of compatibilizer.

[0008] Furthermore, the static dissipative agent is one or more of conductive carbon black, activated carbon fiber, and conductive filler carbon nanotube.

[0009] Furthermore, the flame retardant is one or more of hexaphenoxy cyclotriphosphazene and bisphenol A-bis(diphenyl phosphate).

[0010] Furthermore, the antioxidant is a hindered phenol antioxidant.

[0011] Furthermore, the toughening agent is one or more of methyl methacrylate-butadiene-styrene toughening agent (MBS), nitrile rubber (NBR), SEBS, SiO2, and CaCO3.

[0012] In a second aspect, the present invention further provides a process for preparing antistatic PC plastic particles.

[0013] The steps include: (1) The raw materials are placed in a constant temperature drying oven and dried for 18-24 hours. The temperature of the constant temperature drying oven is set at 50-110 degrees Celsius; (2) Take out the raw materials in the constant temperature drying oven, weigh the corresponding mass together with the other raw materials that do not need to be dried, add them into the twin-screw extruder according to the proportion, and carry out heating and melting, plasticizing and mixing, cooling and solidification, extrusion granulation, separation and screening, and packaging and storage operations; (3) Dry the obtained plastic particles in a constant temperature drying oven at 100 degrees Celsius for 4-6 hours, and form standard specimens through an injection molding machine; (4) Take out the prepared standard specimen and let it stand for 24 hours before measuring the material indicators.

[0014] Furthermore, the process parameters of the twin-screw extruder are: The temperature of zone 1 is 120-140 degrees Celsius, the temperature of zone 2 is 250-260 degrees Celsius, the temperature of zone 3 is 250-260 degrees Celsius; the temperature of zone 4 is 240-250 degrees Celsius; the temperature of zone 5 is 240-250 degrees Celsius; the temperature of zone 6 is 230-250 degrees Celsius; the temperature of zone 7 is 235-250 degrees Celsius; the temperature of zone 8 is 240-250 degrees Celsius; the temperature of zone 9 is 240-250 degrees Celsius; The head temperature is 235 degrees Celsius; the pressure is 29-36 MPa; the main engine speed is 220-300 r / min; the feeding speed is 100-150 r / min; and the pelletizing speed is 250-300 r / min.

[0015] Furthermore, the process parameters of the injection molding machine are: The temperature is 270-290 degrees Celsius, the injection pressure is 80-150 MPa, the back pressure is 15-25 MPa, the holding pressure is 50-100 MPa, the residence time is 20-80s, the cooling time is 15-30s, and the injection time is 2-6s.

[0016] Furthermore, the material indicators include material density, mechanical properties, flame retardancy, antistatic properties and melt fluidity.

[0017] The beneficial effects of the present invention are: (1) The present invention prepares an antistatic PC plastic particle. By integrating PC with PMMA, the plastic particle product can resist corrosion by various chemical substances such as acid, alkali, and salt. Scanning electron microscope images show that after being corroded by various chemical substances such as acid, alkali, and salt, a large area of ​​the surface of the plastic particle is still relatively flat.

[0018] (2) The antistatic PC plastic particles prepared by the present invention have better fluidity during processing by integrating PC into PETG, which helps to reduce stress concentration and defects inside the plastic particle products, thereby improving the mechanical properties and service life of the plastic particle products.

[0019] (3) The antistatic PC plastic particles prepared by the present invention include a combination of an electrostatic dissipative agent and a flame retardant, which prevents the flame retardant molecules from reducing the tensile strength and bending strength of the plastic particles and simultaneously enhances the antistatic property of the plastic particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a process flow chart for preparing antistatic PC plastic particles of the present invention; Figure 2 The effect of the particle size of CaCO3 used in the present invention on the tensile strength and impact strength of plastic particles; Figure 3 The results of the corrosion resistance test of Example 1 (left) and Comparative Example 1 (right) to acids, bases and salts are shown; Figure 4 is a scanning electron microscope image of the carbon fiber used in the present invention; Figure 5 This is a scanning electron microscope image of an antistatic PC plastic particle of the present invention after being corroded by acid, alkali or salt. DETAILED DESCRIPTION

[0021] The following is a detailed description of embodiments of the present invention, but the present invention can be implemented in many different ways as defined and covered by the claims.

[0022] Example 1 A formula of plastic particles for processing electrical product housings: 50 parts of polycarbonate, 25 parts of PMMA, 25 parts of PETG, 5 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 10 parts of flame retardant, 4 parts of toughening agent, and 8 parts of compatibilizer.

[0023] Furthermore, the static dissipative agent is activated carbon fiber. Carbon fiber is a material with excellent conductive properties. Its conductivity mainly comes from its internal graphite microcrystalline structure. This structure enables the carbon fiber to significantly improve the conductive properties of the composite material at a lower addition amount. In some electrical products, in addition to being insulating, the outer shell also needs to have antistatic properties to prevent damage or malfunctions caused by static electricity accumulation and discharge. For example, in the fields of integrated circuit packaging, electromagnetic wave shielding, etc., there are high requirements for the antistatic properties of the material. Adding an appropriate amount of static dissipative agent can significantly reduce the surface resistance of the PC material, thereby solving the static electricity problem in production and use.

[0024] Furthermore, the antioxidant is antioxidant 1076, which inhibits or delays the aging of PC plastic during processing and use by capturing free radicals, decomposing peroxides, etc., thereby maintaining its good performance. Antioxidant 1076 usually has low toxicity and good thermal stability, and can effectively protect PC plastic from the influence of thermal oxidative aging.

[0025] Furthermore, the lubricant is ethylene bisstearamide, which also acts as a dispersant. The polymer usually has a high viscosity after melting. The friction and adhesion between particles and between particles and equipment during processing will affect production efficiency and product quality. Ethylene bisstearamide can reduce these frictions and reduce the interfacial adhesion performance, making the plastic particles smoother during processing, and at the same time making the additives more evenly distributed in the plastic particles, preventing the particles from agglomerating, and playing the role of a dispersant.

[0026] Furthermore, the flame retardant is hexaphenoxy cyclotriphosphazene, which is easily soluble in ketones and aromatic hydrocarbon solvents, has good compatibility with polymer compounds, is easy to add during the manufacturing process, has high flame retardant properties, and does not emit toxic or corrosive gases when burned, and is more environmentally friendly and healthy.

[0027] Furthermore, the toughening agent includes CaCO3 and SEBS. The synergistic effect of CaCO3 and SEBS can significantly improve the comprehensive performance of PC materials, such as toughness, strength, heat resistance, processing fluidity, etc. CaCO3 mainly provides rigidity, thermal stability and cost-effectiveness, while SEBS mainly provides toughness, aging resistance and weather resistance. The combination of the two can give full play to their respective advantages and form a complementary effect. The decomposition temperature of CaCO3 is above 800°C, which does not affect the processing temperature of plastics and can improve the temperature resistance of products during use.

[0028] Furthermore, some of the CaCO3 have a particle size d<0.1 μm. Ultrafine or nanoscale CaCO3 can significantly improve the impact resistance of the material in the high molecular polymer, and also has an improving effect on the tensile strength and elongation at break.

[0029] The preparation process is as follows: (1) Raw material preparation and pretreatment: the raw materials are placed in a constant temperature drying oven and dried for 20 hours, with the drying temperature of PC at 110 degrees Celsius, the drying temperature of PETG at 75 degrees Celsius, and the drying temperature of PMMA at 60 degrees Celsius. The acyl groups in PC materials are easily hydrolyzed with water to produce acidic substances. This hydrolysis reaction will cause the molecular chain of PC materials to break, thereby affecting the quality of the products. After these raw materials are dried, they are easier to flow and fill the mold during the injection molding process, thereby improving production efficiency. After the water is removed, the quality and performance of the final product can be ensured, and defects such as yellowing, silver streaks, bubbles, and shrinkage holes can be avoided; (2) Feeding and conveying: Take out the raw materials from the constant temperature drying oven, weigh the corresponding mass portions together with the other raw materials that do not need to be dried, and convey them to the feeding port of the twin-screw extruder through a screw feeder. The feeding speed is 120r / min; (3) Heating and melting: the raw material particles are heated and melted in the twin-screw extruder to form a uniform plastic melt. During this process, the main engine speed is 260 r / min; (4) Plasticizing and mixing: The threads on the screw shear, extrude, and convey the material. Under the combined action of heating and shearing force, the material gradually melts and plasticizes, and is fully mixed. The meshing structure of the twin screws helps to distribute and disperse the material; (5) Cooling and solidification: the material after plasticization and mixing is pushed to the die head, extruded through the specific hole pattern on the die to form a strip-shaped material, and then quickly cooled and solidified by underwater cooling; (6) Extrusion granulation, using a pelletizing device to cut the strip material into pellets of the required length; (7) Separation and screening: placing the cooled particles into a vibrating screening machine for screening and separation to obtain finished particles that meet the specifications; (8) Packaging and storage: Qualified finished particles are dried in a constant temperature drying oven at 100 degrees Celsius for 6 hours, and then the processed plastic particles are packaged and stored in a dry and cool environment to prevent moisture and deterioration; (9) Randomly select product samples, dry them in a constant temperature drying oven at 100 degrees Celsius for 5 hours, and use an injection molding machine to make standard specimens; (10) After the standard specimen is prepared, let it stand for 24 hours before measuring the material index.

[0030] Furthermore, the process parameters of the injection molding machine are: The temperature of zone 1 is 290 degrees Celsius; the temperature of zone 2 is 260 degrees Celsius; the temperature of zone 3 is 260 degrees Celsius; the temperature of zone 4 is 270 degrees Celsius; the temperature of zone 5 is 285 degrees Celsius; the injection pressure is 120 MPa, the back pressure is 20 MPa, the holding pressure is 80 MPa, the residence time is 60 s, the cooling time is 25 s, and the injection time is 5 s.

[0031] Furthermore, the material indicators include material density, mechanical properties, flame retardancy, antistatic properties and melt fluidity.

[0032] Furthermore, the density test was carried out according to GB / T 1033.1-2008, and each sample was repeated 3 times to take the average value.

[0033] Furthermore, the mechanical properties include tensile strength, flexural strength and impact strength. The tensile properties are tested in accordance with ISO 527.2-2012 "Plastics-Determination of tensile properties Part 2: Test conditions for molded and extruded plastics", and each sample is repeated 3 times to take the average value; the flexural properties are tested in accordance with ISO 178-2019 "Plastics-Determination of flexural properties", and each sample is repeated 3 times to take the average value; impact strength: according to ISO 179.2-2020 "Plastics-Determination of impact properties of simply supported beams Part 2: Instrumented impact test", each sample is repeated 3 times and the average value is taken.

[0034] Furthermore, the flame retardant properties include vertical burning properties and horizontal burning properties, which are tested in accordance with GB / T 2408-2021 "Horizontal and vertical methods for determination of burning properties of plastics", and each sample is repeated 3 times to take the average value.

[0035] Furthermore, the antistatic performance is characterized by surface resistance, which is tested according to GB / T 1410-2006, with each sample repeated 3 times to take the average value.

[0036] Furthermore, the melt flowability is characterized by melt index (MFR), and the melt index test method is as follows: The temperature of the melt indexer is raised to 250℃. Each group of samples after pelletizing is added into the trough. The piston is covered and the samples are heated and melted in the trough for 5 minutes. Then, weights are added to keep the total load at 2.16kg. When the melt flows out evenly and reaches the scale line, automatic cutting begins, 3s / time, for a total of 5 times. The mass of the 5 segments of melt is calculated. The melt index (MFR) can be obtained by the following formula: MFR=600 / T×W MFR is the melt index, in g / 10min; T is the cutting interval time, unit is s; W is the average mass of the melt in five sections, in g; Each sample was repeated 3 times and the average value was taken.

[0037] Example 2 Compared with Example 1, the only difference in Example 2 is that the formula of the plastic particles is different: 50 parts of polycarbonate, 25 parts of PMMA, 25 parts of PETG, 5 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 10 parts of flame retardant, 4 parts of toughening agent, and 8 parts of compatibilizer.

[0038] Furthermore, the static dissipative agent is conductive filler carbon nanotubes.

[0039] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0040] Example 3 Compared with Example 1, the only difference in Example 3 is that the formula of the plastic particles is different: 50 parts of polycarbonate, 25 parts of PMMA, 25 parts of PETG, 5 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 10 parts of flame retardant, 4 parts of toughening agent, and 8 parts of compatibilizer.

[0041] Furthermore, the flame retardant is bisphenol A-bis(diphenyl phosphate).

[0042] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0043] Example 4 Compared with Example 1, the only difference in Example 4 is that the formula of the plastic particles is different: 50 parts of polycarbonate, 25 parts of PMMA, 25 parts of PETG, 5 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 10 parts of flame retardant, 4 parts of toughening agent, and 8 parts of compatibilizer.

[0044] Furthermore, the static dissipative agent is conductive filler carbon nanotubes.

[0045] Furthermore, the flame retardant is bisphenol A-bis(diphenyl phosphate).

[0046] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0047] Example 5 Compared with Example 1, the only difference in Example 5 is that the formula of the plastic particles is different: 60 parts of polycarbonate, 20 parts of PMMA, 20 parts of PETG, 5 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 10 parts of flame retardant, 4 parts of toughening agent, and 8 parts of compatibilizer.

[0048] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0049] Example 6 Compared with Example 1, the only difference in Example 6 is that the formula of the plastic particles is different: 40 parts of polycarbonate, 30 parts of PMMA, 30 parts of PETG, 5 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 10 parts of flame retardant, 4 parts of toughening agent, and 8 parts of compatibilizer.

[0050] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0051] Example 7 Compared with Example 1, the only difference in Example 7 is that the formula of the plastic particles is different: 70 parts of polycarbonate, 15 parts of PMMA, 15 parts of PETG, 5 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 10 parts of flame retardant, 4 parts of toughening agent, and 8 parts of compatibilizer.

[0052] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0053] Example 8 Compared with Example 1, the only difference in Example 8 is that the formula of the plastic particles is different: 50 parts of polycarbonate, 25 parts of PMMA, 25 parts of PETG, 10 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 10 parts of flame retardant, 4 parts of toughening agent, and 8 parts of compatibilizer.

[0054] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0055] Example 9 Compared with Example 1, the only difference in Example 9 is that the formula of the plastic particles is different: 50 parts of polycarbonate, 25 parts of PMMA, 25 parts of PETG, 1 part of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 10 parts of flame retardant, 4 parts of toughening agent, and 8 parts of compatibilizer.

[0056] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0057] Example 10 Compared with Example 1, the only difference in Example 10 is that the formula of the plastic particles is different: 50 parts of polycarbonate, 25 parts of PMMA, 25 parts of PETG, 5 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 6 parts of flame retardant, 4 parts of toughening agent, and 8 parts of compatibilizer.

[0058] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0059] Embodiment 11 Compared with Example 1, the only difference in Example 11 is that the formula of the plastic particles is different: 50 parts of polycarbonate, 25 parts of PMMA, 25 parts of PETG, 5 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 15 parts of flame retardant, 4 parts of toughening agent, and 8 parts of compatibilizer.

[0060] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0061] Example 12 Compared with Example 1, the only difference in Example 12 is that the formula of the plastic particles is different: 50 parts of polycarbonate, 25 parts of PMMA, 25 parts of PETG, 5 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 10 parts of flame retardant, 2 parts of toughening agent, and 8 parts of compatibilizer.

[0062] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0063] Embodiment 13 Compared with Example 1, the only difference in Example 12 is that the formula of the plastic particles is different: 50 parts of polycarbonate, 25 parts of PMMA, 25 parts of PETG, 5 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 10 parts of flame retardant, 5 parts of toughening agent, and 8 parts of compatibilizer.

[0064] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0065] Comparative Example 1 Compared with Example 1, the only difference in Comparative Example 1 is that the formula of the plastic particles is different: 50 parts of polycarbonate, 0 parts of PMMA, 25 parts of PETG, 5 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 10 parts of flame retardant, 4 parts of toughening agent, and 8 parts of compatibilizer.

[0066] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0067] Comparative Example 2 Compared with Example 1, the only difference in Comparative Example 2 is that the formula of the plastic particles is different: 50 parts of polycarbonate, 25 parts of PMMA, 0 parts of PETG, 5 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 10 parts of flame retardant, 4 parts of toughening agent, and 8 parts of compatibilizer.

[0068] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0069] Comparative Example 3 Compared with Example 1, the only difference in Comparative Example 3 is that the formula of the plastic particles is different: 50 parts of polycarbonate, 25 parts of PMMA, 25 parts of PETG, 0 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 10 parts of flame retardant, 4 parts of toughening agent, and 8 parts of compatibilizer.

[0070] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0071] Comparative Example 4 Compared with Example 1, the only difference in Comparative Example 4 is that the formula of the plastic particles is different: 50 parts of polycarbonate, 25 parts of PMMA, 25 parts of PETG, 5 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 0 parts of flame retardant, 4 parts of toughening agent, and 8 parts of compatibilizer.

[0072] Comparative Example 5 Compared with Example 1, the only difference in Comparative Example 5 is that the formula of the plastic particles is different: 50 parts of polycarbonate, 25 parts of PMMA, 25 parts of PETG, 5 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 10 parts of flame retardant, 0 parts of toughening agent, and 8 parts of compatibilizer.

[0073] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0074] Comparative Example 6 Compared with Example 1, the only difference in Comparative Example 6 is that the formula of the plastic particles is different: 50 parts of polycarbonate, 25 parts of PMMA, 25 parts of PETG, 0 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 0 parts of flame retardant, 4 parts of toughening agent, and 8 parts of compatibilizer.

[0075] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0076] Comparative Example 7 Compared with Example 1, the only difference in Comparative Example 6 is that the formula of the plastic particles is different: 50 parts of polycarbonate, 25 parts of PMMA, 25 parts of PETG, 0 parts of static dissipative agent, 0.5 parts of antioxidant, 0.5 parts of lubricant, 10 parts of flame retardant, 0 parts of toughening agent, and 8 parts of compatibilizer.

[0077] The preparation process and other related parameters of this embodiment are consistent with those of embodiment 1.

[0078] Table 1 Composite material density and mechanical properties test data Combining the data of Example 1 to Example 4, it can be seen that when the static dissipative agent is 5 parts and the flame retardant is 10 parts, the types of static dissipative agent and flame retardant have almost no effect on the density of the composite material; from the data of Example 1, Example 5 to Example 7 and Comparative Example 1 and Comparative Example 2, it can be seen that the ratio of polycarbonate, PMMA and PETG in the raw materials will have a greater impact on the density of the composite material, mainly because the order of the density of the three materials from large to small is: PETG>PC>PMMA, when the proportion of high-density materials is high, the density of the composite material is increased, and when the proportion of low-density materials is high, the density of the composite material is decreased; combining all the data, it can be seen that the three raw materials of polycarbonate, PMMA and PETG have a greater impact on the density of the composite material, and the other additives have almost no effect on the density of the composite material; Combined with the data of Example 1-Example 4, it can be seen that when carbon fiber is used as an electrostatic dissipative agent, the reinforcing effect on the tensile strength, flexural strength and impact strength of the composite material is stronger than that of the conductive filler carbon nanotubes, and bisphenol A-bis (diphenyl phosphate) as a flame retardant has a stronger effect on reducing the tensile strength, flexural strength and impact strength of the composite material than hexaphenoxy cyclotriphosphazene. The combination of conductive filler carbon nanotubes and bisphenol A-bis (diphenyl phosphate) further reduces the tensile strength, flexural strength and impact strength of the composite material; Combined with the data of Example 1, Example 5-Example 7 and Comparative Example 1 and Comparative Example 2, it can be seen that when 50 parts of polycarbonate, 25 parts of PMMA, and PETG When the amount of the composite material is 25 parts, the tensile strength, flexural strength and impact strength of the composite material all reach the highest values, and the raw material ratio effect is the best at this time. When polycarbonate is only combined with PMMA or PETG, the tensile strength, flexural strength and impact strength are not as good as the raw material ratio effect corresponding to Example 1; Combining the data of Example 1, Example 8-Example 13 and Comparative Example 3-Comparative Example 7, it can be seen that the static dissipative agent, flame retardant and toughening agent will affect the mechanical properties of the composite material when they exist alone, among which the flame retardant will significantly reduce the tensile strength, flexural strength and impact strength of the composite material. With the increase of the amount of flame retardant added, the mechanical properties of the composite material show a downward trend, and the toughening agent The addition of will alleviate the effect of flame retardant on the mechanical properties of composite materials. The effect size is related to the amount of toughening agent added. The numerical change of the mechanical properties of the composite material is proportional to the amount of toughening agent added. The static dissipative agent itself has a relatively small effect on the mechanical properties of the composite material, but the combination of static dissipative agent and flame retardant can offset the flame retardant's effect on the mechanical properties of the composite material, while playing the role of toughening agent. When the amount of static dissipative agent added is insufficient, the flame retardant can still reduce the tensile strength, flexural strength and impact strength of the composite material to a certain extent. This is because the static dissipative agent is carbon fiber. In addition to having excellent conductive properties, the carbon fiber has been activated and has a rich microporous structure, such as Figure 4 As shown in the figure, these micropores provide a large number of adsorption sites, allowing carbon fibers to adsorb a large number of flame retardant molecules. In this way, the contact between the flame retardant and the main raw materials polycarbonate, PMMA and PETG is limited, which minimizes the change in the molecular structure and composition of the composite material, greatly reducing the effect of the flame retardant on the mechanical properties of the composite material.

[0079] Table 2 Test data of flame retardancy, melt fluidity and antistatic properties of composite materials Combined with the data of Example 1-Example 4, it can be seen that the flame retardant hexaphenoxy cyclotriphosphazene has a better flame retardant enhancing effect on the composite material than the flame retardant bisphenol A-bis(diphenyl phosphate), the electrostatic dissipative agent is a conductive filler carbon nanotube or carbon fiber has little effect on the flame retardancy of the composite material, and the type of electrostatic dissipative agent has almost no effect on the MFR value, but compared with bisphenol A-bis(diphenyl phosphate), hexaphenoxy cyclotriphosphazene has an optimization effect on the melt fluidity of the composite material, and the carbon fiber improves the antistatic ability of the composite material better than the conductive filler carbon nanotube; Combined with the data of Example 1, Example 5-Example 7 and Comparative Example 1 and Comparative Example 2, it can be seen that the relationship between the main raw materials polycarbonate, PMMA and PETG will also affect the flame retardant properties of the composite material. When the polycarbonate is 40-50 parts, PMMA is 25-30 parts, and PETG is 25-30 parts, the flame retardant grade of the composite material reaches V-0, and the LOI% reaches 32% and above. When the specific polycarbonate is 50 parts, PMMA is 25 parts, and PETG is 10 parts. When the amount of flame retardant added is 25 parts, the antistatic ability of the composite material is the best, and PETG dominates the melt fluidity of the composite material. With the increase of the amount of PETG added, the melt fluidity of the composite material gradually increases. After PETG is added to 25 parts, the melt fluidity of the composite material no longer increases; combined with the data of Example 1, Example 8-Example 13 and Comparative Example 3-Comparative Example 7, it can be seen that with the increase of the amount of flame retardant added, the LOI% of the composite material gradually increases, but after the flame retardant is added to 10 parts or more, the LOI% of the composite material is not much different, and the flame retardant, toughening agent and static dissipative agent have almost no effect on the melt fluidity of the composite material.

Claims

1. A formula of antistatic PC plastic particles, characterized in that: The formula is calculated by weight, and its raw materials include the following components: 40-70 parts of polycarbonate, 15-40 parts of PMMA, 15-40 parts of PETG, 1-10 parts of static dissipative agent, 0.1-0.6 parts of antioxidant, 0.2-1 parts of lubricant, 6-15 parts of flame retardant, 2-5 parts of toughening agent, and 2-10 parts of compatibilizer.

2. The formula of an antistatic PC plastic particle according to claim 1, characterized in that: The static dissipative agent is one or more of conductive carbon black, activated carbon fiber, and conductive filler carbon nanotube.

3. The formula of an antistatic PC plastic particle according to claim 1, characterized in that: The flame retardant is one or more of hexaphenoxy cyclotriphosphazene and bisphenol A-bis(diphenyl phosphate).

4. The formula of the antistatic PC plastic particles according to claim 1, characterized in that: The toughening agent is one or more of methyl methacrylate-butadiene-styrene toughening agent (MBS), nitrile rubber (NBR), SEBS, SiO2, and CaCO3.

5. A process for preparing antistatic PC plastic particles, using the formula of antistatic PC plastic particles according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. The raw materials are placed in a constant temperature drying oven and dried for 18-24 hours. The temperature of the constant temperature drying oven is set at 50-110 degrees Celsius; S2, take out the raw materials in the constant temperature drying oven, weigh the corresponding mass together with the other raw materials that do not need to be dried, add them into the twin-screw extruder according to the proportion, and perform heating and melting, plasticizing and mixing, cooling and solidification, extrusion granulation, separation and screening, and packaging and storage operations; S3, drying the obtained plastic particles in a constant temperature drying oven at 100 degrees Celsius for 4-6 hours, and forming standard specimens through an injection molding machine; S4. Take out the prepared standard sample and let it stand for 24 hours before measuring the material index.

6. The process for preparing antistatic PC plastic particles according to claim 5, characterized in that: The process parameters of the twin-screw extruder are as follows: the temperature of zone 1 is 120-140 degrees Celsius, the temperature of zone 2 is 250-260 degrees Celsius, the temperature of zone 3 is 250-260 degrees Celsius; the temperature of zone 4 is 240-250 degrees Celsius; the temperature of zone 5 is 240-250 degrees Celsius; the temperature of zone 6 is 230-250 degrees Celsius; the temperature of zone 7 is 235-250 degrees Celsius; the temperature of zone 8 is 240-250 degrees Celsius; the temperature of zone 9 is 240-250 degrees Celsius; the head temperature is 235 degrees Celsius; The pressure is 29-36 MPa; the main machine speed is 220-300 r / min; the feeding speed is 100-150 r / min; the pelletizing speed is 250-300 r / min.

7. The process for preparing antistatic PC plastic particles according to claim 6, characterized in that: The process parameters of the injection molding machine are: temperature of 270-290 degrees Celsius, injection pressure of 80-150 MPa, back pressure of 15-25 MPa, holding pressure of 50-100 MPa, residence time of 20-80s, cooling time of 15-30s, and injection time of 2-6s.

Citation Information

Patent Citations

  • A conductive PC composite material

    CN104744908A

  • PC / PMMA / PETG ternary alloy material and preparation method thereof

    CN108676341A

  • Flame-retardant photodiffusion polyester material and preparation method and application thereof

    CN109438930A

  • Polycarbonate alloy as well as preparation method and application thereof

    CN117866405A

  • Scratch-Resistant Flameproof Thermoplastic Resin Composition

    US20090118402A1